KEPEMIMPINAN TRANSAKSIONAL DAN TRANSFORMASIONAL GURU DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA PADA SMA NEGERI 1 SEUNAGAN KABUPATEN NAGAN RAYA - Khairul Zami; Cut Zahri Harun; Khairuddin . (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2018)
Teachers play an important role to improve education quality through increasing their student’s motivation. The purpose of this study was to investigate the leadership style, factors, and obstacles of the transactional and transformational leadership style of the teacher in improving students’ learning motivation at SMA no. 1 of Seunagan, Nagan Raya Regency. This study used descriptive qualitative approach. Data collection techniques used were observation, interviews, and documentation. The research subjects in this study were a principal and teachers. The results of the study showed that (1) Transactional and transformational leadership style of teacher was carried out as full range leadership model in teaching learning process; (2) Factors influencing teacher as transactional and transformational leadership were character, experience, commitment and his/her competency; (3) The obstacle faced by the teachers in implementing transactional and transformational leadership was the lack of parents support toward policies taken by the teacher in determining rewards or sanction on the students.Keywords: teacher, transactional and transformational leadership, student’s learning motivation